Optimizing the traditional cake business of Adee Kak Na: Enhancing product shelf life and digital-based business management - Agustina Nurul Fajriah; Mayang Murni; Muhammad Khalil (Community Empowerment, 2024)
This community service program aims to address the key challenges faced by the Adee Kak Na MSME, including the short shelf life of Adee cake, as well as suboptimal financial management and marketing strategies. The activities focus on improving product shelf life, production efficiency, better financial management, and expanding market reach. The methods applied include innovative food processing techniques to transform Adee cake ingredients into ready-to-use flour to extend product shelf life, basic financial management training to separate business and household finances, and digital marketing training that encompasses branding, packaging, and promotion through social media. The results show that the implementation of food processing techniques successfully doubled the product's shelf life and accelerated the production process. Financial management training helped the partner structure their cash flow records and improve financial oversight. Additionally, digital marketing training enhanced product appeal, expanded market reach, and introduced Adee cake to consumers via social media platforms. Overall, this program significantly increased the competitiveness of Adee Kak Na MSME while supporting the preservation of traditional Acehnese culinary heritage in the digital era.